2014
DOI: 10.1177/0010836714537633
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking ‘policebuilding’

Abstract: In recent years, policebuilding has moved centre stage in international security. Not only have the numbers of police officers deployed externally significantly increased in the last decade, but the police have also come to be regarded as key with regard to the stabilizing of weak or failed states. It is hereby assumed that the police, as a civilian force, are better trained and equipped to establish order and stability than the military. This article challenges such a military-police divide, according to whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Those units are specialized and trained to respond to high-end violent infractions on society, such as terrorist attacks and armed violence (Kraska, 2007; Kraska & Cubelis, 1997; Kraska & Kappeler, 1997). Counterterrorism and counterintelligence—traditional military concepts—are not uncommon for today’s police organizations, neither at home nor during deployment in far-flung regions, as previous studies have shown (Heiduk, 2015; Lutterbeck, 2005).…”
Section: The Military and Police “Divide”mentioning
confidence: 85%
See 1 more Smart Citation
“…Those units are specialized and trained to respond to high-end violent infractions on society, such as terrorist attacks and armed violence (Kraska, 2007; Kraska & Cubelis, 1997; Kraska & Kappeler, 1997). Counterterrorism and counterintelligence—traditional military concepts—are not uncommon for today’s police organizations, neither at home nor during deployment in far-flung regions, as previous studies have shown (Heiduk, 2015; Lutterbeck, 2005).…”
Section: The Military and Police “Divide”mentioning
confidence: 85%
“…Historically, the divide between the police and the military has not always been large. Napoleon’s gendarmerie and British colonial troops are examples of forces that transcended the police–military gap on a European and even worldwide scale (e.g., Brodeur, 2010; Heiduk, 2015; Lutterbeck, 2004). Since the rise of the nation-state, the emergence of the mass armies, and the professionalization of the police organization in the late 18th and early 19th century, a clearer operational and organizational demarcation slowly developed, making the police responsible for internal security and the military for external security (e.g., Bayley, 1985).…”
Section: The Military and Police “Divide”mentioning
confidence: 99%
“…However, current challenges (more complex, unpredictable and asymmetric) have further reduced old threats to EU security and have shown that more knowledge is needed about emerging phenomena such as hybrid threats, radicalisation, organised crime, border management and maritime security. In this sense, to strengthen European security and defence, it is key to understand a multiplicity of factors such as the transatlantic burden-sharing approach of the US administration, and new regional and global actors (Heiduk, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the military, police and paramilitary have different roles, the treatment of civilians in different crisis/conflict scenarios is expectedly different. A tongue in cheek conceptualization of the issue was summed up as ‘police officers … [are] … better prepared to work with a population to help it achieve internal security; soldiers … [are] … trained … to break things and kill people’ (Marten, 2007, p. 242 cited in Heiduk, 2015, p. 72).…”
Section: Positive State Action At the Micro-levelmentioning
confidence: 99%